A Comparative Study on Red and White Karkade (Hibiscus sabdariffa L.) Calyces, Extracts and Their Products - Suliman, Abdallah M.A.; Ali, Ali O.; A.A. Idriss, Sharaf Eldeen; Abdualrahman, Mohammed A.Y. (Pakistan Journal of Nutrition, 2011)
This study dealt with red and white karkade calyces (Hibiscus sabdariffa L.) which are found in different parts of the world especially, the tropical and subtropical areas. In Sudan karkade is grown in western parts of the country (Kordofan and Darfur). In this study the chemical composition of dry red and white Roselle calyces was studied. It was found that, the red and white karkade calyces were contained 11 and 9.3% moisture respectively. Also the following was found respectively, 0.16 and 0.12% (fat), 13.2 and 12% (fiber), 7.88 and 7.35% (protein), 10.6 and 9.5% (ash) and 57.16 and 61.55% (carbohydrates). The red and white karkade calyces were also contained 11 and 15.5 mg/100 g of vitamin C, 60 and 50 mg/100 g of calcium, 25 and 20 mg/100 g of iron and 9 and 11 mg/100 g titrable acidity, respectively. Extraction of karkade calyces was carried out using different soaking ratios ranging from 1:6 to 1:12 and different soaking periods ranging from 1-4 h. For cold extraction the best soaking ratios and soaking period for red karkade were 1:10 for 2 h and ratio of 1:12 for 3 h for white karkade. Cold and hot drinks as well as jams and marmalades were made from both types of Roselle extracts. All these products were subjected to sensory analysis and tested for preference by sensory panels using hedonic scale. The sensory evaluation of cold and hot drinks made from both kinds of red and white karkade revealed that there was no significant difference as regard to the overall preference. The sensory evaluation of jams showed that there were no difference according to it is appearance, color, flavor and overall acceptability. However, there were differences in consistency.